1999
DOI: 10.1021/ma981949x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Effects of Microphase Separation on the Permselectivity for Aqueous Ethanol Solutions of Block and Graft Copolymer Membranes Containing Poly(dimethylsiloxane)

Abstract: The permselectivity of block copolymer membranes consisting of ethanol-permselective poly(dimethylsiloxane) (PDMS) plus water-permselective poly(methyl methacrylate) (PMMA) was compared to the permselectivity of graft copolymer membranes for the separation of an aqueous ethanol solution. This paper focuses on the difference in molecular architecture between the block and graft copolymers and relates microphase separation in these membranes to their permeability and permselectivity for an aqueous ethanol soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 33 publications
4
43
0
1
Order By: Relevance
“…Other methods have been reported for the synthesis of PDMS-b-PMA by combining anionic with group transfer, 10 atom transfer radical, 11 or free radical polymerization. 12 The above procedures (refs 10-12) lead to materials with high molecular and compositional polydispersity.An alternative and perhaps more versatile approach for the synthesis of block copolymers would be one that employs a linking agent with two different functional groups (heterofunctional linking agent). The reactivity of the two groups should be different toward dissimilar macroanions.…”
mentioning
confidence: 99%
“…Other methods have been reported for the synthesis of PDMS-b-PMA by combining anionic with group transfer, 10 atom transfer radical, 11 or free radical polymerization. 12 The above procedures (refs 10-12) lead to materials with high molecular and compositional polydispersity.An alternative and perhaps more versatile approach for the synthesis of block copolymers would be one that employs a linking agent with two different functional groups (heterofunctional linking agent). The reactivity of the two groups should be different toward dissimilar macroanions.…”
mentioning
confidence: 99%
“…Uragami et al revealed that the continuity of the ODMS phase in the microphase separation strongly influenced the ethanol permselectivity of block and graft copolymers containing ODMS segment, and the percolation transition of the ODMS phase took place at a ODMS content of about 35 mol % (28 wt %) in ODMS-grafted poly-(methyl methacrylate) membrane. 11 The ODMS contents of PAI/ODMS-1 and 3, which were 29.5 and 27.1 wt %, respectively, would cause a boundary morphological effect to exhibit the ethanol permselectivity. On the contrary, PAI/ODMS-1 membrane exhibited unexpectedly the higher selectivity for aqueous acetone permeation than PAI/ODMS-3 membrane.…”
Section: Pervaporation Results Of Pai/odms Graft Copolymer Membranesmentioning
confidence: 99%
“…14 Recently, glassy materials have gained importance [15][16][17] with respect to which there are reports of using blends of poly(methyl methacrylate) (PMMA) with cellulose acetate, 18 bisphenol chloral polycarbonate, 19 poly(vinylidene fluoride) (PVDF), 20 and poly(dimethylsiloxane) (PDMS) grafted PMMA. 21,22 Separation depends on the properties of the surface and is affected by such physicochemical properties as pore size, wetdiation grafting, 24 surface oxidation, 25 plasma-phase reaction, [26][27][28][29] and copolymerization. Gancarz et al modified the ultrafiltration polysulfone membranes by plasma treatment using CO 2 , 26 acrylic acid, 27 nitrogen, 28 and ammonia 29 and showed an increase in the pore size and wettability.…”
Section: Introductionmentioning
confidence: 99%